Mechanical and thermal properties of binary blends poly lactic acid (PLA) and recycled high-density polyethylene (rHDPE) - Aishah, N.; Mohd Bijarimi, Mat Piah; Moshiul, A. K. M.; Mohd Shaiful Zaidi, Mat Desa; Norazmi, M.; Alhadadi, W.; Hafizah, F.; Mohd Zulkifli, Mohamad Noor (IOP Publishing, 2020)
In this work, plastic bottles made of high-density polyethene (HDPE) have been recycled and blended with poly(lactic acid) (PLA). The aim of the work is to prepare a binary blend of PLA and Recycled HDPE (rHDPE) at 90:10 blend ratio by using a twin-screw extruder. The blends were compression moulded and characterized in terms of mechanical and thermal properties. It was found that the rHDPE increased the tensile modulus of the binary blend. Fracture morphology demonstrated that the blend of rHDPE and PLA is immiscible. In terms of thermal property, as measured by Differential Scanning Calorimetry (DSC), the glass transition temperature of the binary blend showed a lower value, whereas the crystallization process was significantly improved.